5 - Le développement du sport de performance au Bénin : de l’analyse d’un modèle à un essai de problématique globale - Gouda, Souaïbou; Kpazaï, Georges (Africa Development, 2021)
The model of the sport development kept in French-speaking black Africa countries was the one of the performance as it has been proposed by the Olympic charter. This charter, by declaring the sport above the politics and of the religion (and until one more recent moment again above the economy), seemed to put forward the idea that sport could be conceived without political, economic and cultural constraints. The present survey aims to show that the development of the performance sport founds on a development global and harmonious correspondent to a certain economic, scientific and technological development level that affects the level and the life style of the population in a satisfactory manner directly.